The response of synthetic 4-hydroxybenzoic acid on kv1.4 potassium channel subunit expressed in xenopus laevis oocytes - Mohamad, Fatin Hilyani (2016)
Extensive researches are being made on natural products especially herbs and plants that have long been practiced in traditional medicines such as Chinese and Ayurvedic that have been used to treat neuronal disorders such as convulsive, dizziness and headaches. 4-hydroxybenzoic acid is a non-flavonoid phenol found abundantly in Dendrocalamus asper shoots (bamboo), fruits (strawberries and apples) and flowers. In this study, the response of synthetic 4-hydroxybenzoic acid was tested on Kv1.4 potassium channel that was expressed in Xenopus laevis oocytes as the model system. Kv1.4 is a rapidly inactivating Shaker-related member of the voltage-gated potassium channels with two inactivation mechanisms; the fast N-type and slow C-type. It plays vital roles in repolarization, hyperpolarization and signaling the restoration of resting membrane potential through the regulation of the movement of K+ across the cellular membrane. cRNA of Kv1.4 prepared during molecular work was injected into viable oocytes that was extracted through surgery at the lower abdomen of X.laevis. The current produced from K ions were detected by the two-microelectrode voltage clamp (TEVC) method, holding potential starting from -80mV with 20mV step-up until +80mV. Readings of treatments with 0.1% DMSO, 4-Hba concentrations and K channel blockers were taken at +60mV. The ratio of tail / peak amplitude is the index of the activity of the Kv1.4 channels with n≥ 6 (number of oocytes tested). Lower ratio signifies lower membrane potential and enhancement of Kv1.4 channel inactivation. The decreases of the ratios of 5 different concentrations (1μM, 10μM, 100μM, 1mM and 2.5mM) were compared with 0.1% DMSO as the control. All concentration showed statistically significant results with p < 0.05 except for 100μM. The normalized current of the 4-hba concentrations were compared with potassium channel blockers (TEA and 4-AP) and all groups showed statistically significant results. This study also showed that time taken for each concentration to affect Kv1.4 does not play any significant roles. In conclusion, 4-hydroxybenzoic acid was found to be able to enhance the inactivation of Kv1.4 by lowering the membrane potential so that the abnormal neuronal firing can be inhibited which can be seen through comparison of DMSO and potassium channel blockers. With IC50 slightly higher than 10μM, increasing concentrations (100μM, 1mM and 2.5mM) had shown to exhibit toxicity effects. The best concentration from this study is 10μM with Hill slope of 0.1799.